IMPLEMENTASI PERATURAN DAERAH KABUPATEN KUTAI KARTANEGARA NOMOR 19 TAHUN 2016 TENTANG RENCANA INDUK PEMBANGUNAN KEPARIWISATAAN DI KABUPATEN KUTAI KARTANEGARA - Rahman Rahman (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This research aims to describe the implementation of tourism development policies in the Tenggarong District, Kutai Kartanegara Regency, and to identify the supporting and inhibiting factors for tourism development efforts in Tenggarong District, Kutai Kartanegara Regency. This research uses descriptive research type with qualitative methods. Later, the data obtained through interview techniques, observation, and documentation will be analyzed with interactive model analysis so that a conclusion can finally be obtained. The results showed that the implementation of tourism development policies in the Tenggarong Subdistrict, Kutai Kartanegara Regency, was running well but not yet effective, especially in the communication process, human resources, budget, birocracy structur and disposition.Keyword: implementation, policy, tourism development